2020
DOI: 10.1007/s00330-019-06503-2
|View full text |Cite
|
Sign up to set email alerts
|

Refining the criteria for immediate total-body CT after severe trauma

Abstract: Objectives Initial trauma care could potentially be improved when conventional imaging and selective CT scanning is omitted and replaced by immediate total-body CT (iTBCT) scanning. Because of the potentially increased radiation exposure by this diagnostic approach, proper selection of the severely injured patients is mandatory. Methods In the REACT-2 trial, severe trauma patients were randomized to iTBCT or conventional imaging and selective CT based on predefined criteria regarding compromised vital paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…WBCT markedly reduces time spent in the emergency department [ 97 ] and a median 19 min from admission to CT was significantly associated with decreased mortality from exsanguination in a single-centre experience [ 98 ]. A revised set of 10 clinical criteria for immediate WBCT with a high-positive predictive value for severe injury based upon secondary analysis of REACT-2 data is shown in Table 3 [ 99 ]. Given the post hoc analysis in a subset of patients on which these data are based, these criteria may not apply to all patients, and a targeted approach may be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…WBCT markedly reduces time spent in the emergency department [ 97 ] and a median 19 min from admission to CT was significantly associated with decreased mortality from exsanguination in a single-centre experience [ 98 ]. A revised set of 10 clinical criteria for immediate WBCT with a high-positive predictive value for severe injury based upon secondary analysis of REACT-2 data is shown in Table 3 [ 99 ]. Given the post hoc analysis in a subset of patients on which these data are based, these criteria may not apply to all patients, and a targeted approach may be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Recent European guidelines recommend the use of early WBCT for the detection of the source of bleeding [9]. However, due to a gap in the evidence concerning the bene t of WBCT in all severely injured patients and concerns with potentially harmful radiation exposure [10], some authors recommend a tailored approach with selective use of WBCT in injured patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested the safety of WBCT and a survival bene t in unstable trauma patients [13], [14], [15],[16], [17],[18], [19], [20]. A second analysis of the REACT-2 trial showed that WBCT led to a strong reduction in mortality in injured patients requiring emergency bleeding control interventions, but failed to demonstrate a statistical signi cance due to an underpowered study [11] [21]. However, in all these studies, the de nition of haemodynamic instability was based on vital signs (systolic blood pressure, heart rate, respiratory rate, Glasgow Coma Scale score) without physiological surrogates of shock leading to heterogeneity in the treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…Each main fracture type is further subdivided into nine first-order subcategories and a total of 26 second-order subcategories [ 16 ]. Although originally designed for use with plain radiographs, the Tile classification is now routinely used based on CT images [ 17 ], which allow for a more precise evaluation of the posterior elements of the pelvic ring [ 18 20 ] and can further aid in identifying bleeding from pelvic sources and associated abdominal injuries [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%